2010
DOI: 10.1021/cm903361y
|View full text |Cite
|
Sign up to set email alerts
|

A New Cross-Linkable Oxygen Sensor Covalently Bonded into Poly(2-hydroxyethyl methacrylate)-co-Polyacrylamide Thin Film for Dissolved Oxygen Sensing

Abstract: A new oxygen sensor, compound 2, was synthesized through a chemical modification of a popularly used oxygen sensor of platinum(II)-5,10,15,20-tetrakis-(2,3,4,5,6-pentafluorophenyl)-porphyrin (PtTFPP). The new sensor compound 2 possesses four crosslinkable methacrylate functional moieties, enabling it to be polymerized and crosslinked with other monomers for polymer sensing film (also called membrane) preparation. Using this characteristic, compound 2 was covalently bonded to hydrophilic poly(2-hydroxyethyl met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 49 publications
6
109
0
Order By: Relevance
“…1, 8.2, 12.3, 16.4, 20.5, 24.6, 28.7, 32.8, 36.9, and 41.0 mg/L respectively. 84 s, respectively [62]. This comparison demonstrated that these micelles are reasonable materials for oxygen sensing.…”
Section: Reversibility and Responsive Time Testmentioning
confidence: 61%
See 1 more Smart Citation
“…1, 8.2, 12.3, 16.4, 20.5, 24.6, 28.7, 32.8, 36.9, and 41.0 mg/L respectively. 84 s, respectively [62]. This comparison demonstrated that these micelles are reasonable materials for oxygen sensing.…”
Section: Reversibility and Responsive Time Testmentioning
confidence: 61%
“…5A), respectively. Recovery times from the air saturated solution to deoxygenated solution were slower with a t 90-r of 100 s and t 95-r of 132 s. These response times were quite faster than those of PtTFPP physically doped in poly(2-hydroxyethyl methacrylate) (PHEMA) matrix and faster than those of PtTFPP physically doped in polystyrene (PS) matrix [62]. The t 95 of PtTFPP in PHEMA and PS matrices from deoxygenated solutions to oxygenated solutions are 50 and 4.…”
Section: Reversibility and Responsive Time Testmentioning
confidence: 97%
“…Carbon monoxide (CO) and carbon dioxide (CO 2 ) [139] gas sensors were fitted in the garments or boots of the people like firefighters for safe measures. Oxygen (O 2 ) sensing systems [140,141] were designed and mounted on the wrist of a person to determine the continuous change in oxygen level is happening in hemoglobin during respiration. Microelectromechanical systems (MEMS) fabrication techniques have been primarily involved to fabrication WFS for biological applications.…”
Section: Sensor Network For Wearable Flexible Sensorsmentioning
confidence: 99%
“…Glucose-sensing hydrogel materials are candidates that would be used as a glucose monitoring system for diabetic patients [136,137]. Researchers have found a suitable category of such material, known as "bio-smart" material, which combines the arti cial molecular identi cation with actuation and contains poly (methyl acrylate) and (hydroxyethyl) methacrylate [138,139]. To use functional hydrogel in diabetic study, when the glucose oxidation enzyme in the presence of oxygen transforms blood sugar to gluconic acid, the local pH value of the bulk medium decreases, where change rises the swelling property of positively charged hydrogels and thus discharges the insulin.…”
Section: Blood-sugar-sensitive Hydrogel Materialsmentioning
confidence: 99%